Spin transport in the three-dimensional XY model with single-ion anisotropy. (September 2018) - Lima, L.S.
Abstract: We analyze the effect of the critical behavior (line that separates the different phases in the graphic D c vs. α, ( α = J 2 ∕ J 1 )) on spin transport in the quantum three-dimensional anisotropic XY model at T = 0. We study the case of the cubic lattice with ion-single anisotropy, considering first neighbors interactions in-plane and out-plane which is an important lattice model of magnetism. We obtain a large variation of the peak of the AC spin conductivity in the range of large values of the critical ion-single anisotropy D c, where the height of the single peak of the spin conductivity suffers a sudden variation in its height. Highlights: The model is studied using the Bond operator method. The spin current of excitons and spin conductivity is calculated using the Kubo formalism of the linear response theory. The effect of critical points (quantum phase transition) on AC spin conductivity is analyzed.